The splendid and the vile : a saga of Churchill, family, and defiance during the Blitz - Larson, Erik, 1954- (New York : Crown, 2020)
A portrait of Winston Churchill and London during the Blitz. On Winston Churchill's first day as prime minister, Hitler invaded Holland and Belgium. This shows in cinematic detail how Churchill taught the British people the art of being fearless.
Bleak expectations -- The rising threat -- A certain eventuality -- Dread -- Blood and dust -- The Americans -- Love amid the flames -- One year to the day -- Epilogue.
Includes bibliographical references (pages 547-554) and index.
Keywords: Churchill, Winston, -- 1874-1965.; Prime ministers -- Great Britain -- Biography; World War, 1939-1945 -- Great Britain; World War, 1939-1945 -- Campaigns -- Great Britain; World War, 1939-1945 -- Social aspects -- Great Britain